Sex disparities in access to caregiving in Parkinson disease. (2nd January 2018) - Dahodwala, Nabila; Shah, Krunal; He, Ying; Wu, Samuel S.; Schmidt, Peter; Cubillos, Fernando; Willis, Allison W.
Abstract : Objective: To compare access to caregiving between men and women with Parkinson disease (PD). Methods: This was a cross-sectional and longitudinal study among participants with PD enrolled in the National Parkinson Foundation Parkinson's Outcomes Project from 2009 to 2014 at 21 international sites. The primary outcome measures were presence of a caregiver at the baseline visit, caregiver burden as measured by the Multidimensional Caregiver Strain Index (MCSI) at baseline, and time to first paid caregiver. Results: A total of 7, 209 participants (63% men, 37% women) with PD were evaluated. Men had a mean age of 66.0 (SD 9.8) years, and women had a mean age of 66.9 (SD 9.7) years. More men than women had a caregiver (88.4% vs 79.4%, p < 0.0001). Caregivers of men reported greater strain than those of women (MCSI score 19.9 vs 16.4, p < 0.0001). These differences persisted after controlling for age, disease stage, number of comorbidities, cognitive and mobility measures, and health-related quality of life. In addition, the odds of caregiver accompaniment at baseline visit were lower for women compared to men (odds ratio 0.76, 95% confidence interval [CI] 0.67–0.86), and women had a faster rate to using a paid caregiver than men (hazard ratio 1.76, 95% CI 1.35–2.28) after controlling for potential confounders. Conclusions: Informal caregiving resources are lower for women than men with PD, despite the finding that their caregivers report less strain than those of men. In addition, women are more likely to use formal, paid caregivers. Strategies to improve access to caregiving, particularly for women, are needed.